2021
DOI: 10.3389/fvets.2021.690346
|View full text |Cite
|
Sign up to set email alerts
|

Feral Swine Commercial Slaughter and Condemnation at Federally Inspected Slaughter Establishments in the United States 2017–2019

Abstract: Feral swine populations in the United States (US) are capable of carrying diseases that threaten the health of the domestic swine industry. Performing routine, near-real time monitoring for an unusual rise in feral swine slaughter condemnation will increase situational awareness and early detection of potential animal health issues, trends, and emerging diseases. In preparation to add feral swine to APHIS weekly monitoring, a descriptive analysis of feral swine slaughter and condemnations was conducted to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The adoption of an integrated hazard control system in meat production remains the cornerstone of achieving effective hazard identification by meat inspectors. Studies concur that the role of primary meat inspection (PMI) should be coupled with capacitating the inspector with training and ensure that slaughter operators are sufficiently skilled with available technology they could implement for the purpose of physical hazards identification during slaughter (Akkina et al 2021). In line with the one health approach, physical hazards, such as protruding sharp bone splinters, must be removed before they possibly hurt slaughter operators and consumers (Paulsen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of an integrated hazard control system in meat production remains the cornerstone of achieving effective hazard identification by meat inspectors. Studies concur that the role of primary meat inspection (PMI) should be coupled with capacitating the inspector with training and ensure that slaughter operators are sufficiently skilled with available technology they could implement for the purpose of physical hazards identification during slaughter (Akkina et al 2021). In line with the one health approach, physical hazards, such as protruding sharp bone splinters, must be removed before they possibly hurt slaughter operators and consumers (Paulsen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, only federally inspected facilities typically accept and slaughter live wild pigs in Texas. Akkina et al (57) reported that between January 1, 2017 and January 4, 2020, the six federally inspected facilities in Texas slaughtered 239,338 wild pigs, which represented nearly 99% of all wild pigs slaughtered in the U.S. at federally inspected facilities during that period (57). According to interviewees with direct knowledge, two of the six Texas facilities slaughter and process the vast majority of wild pigs.…”
Section: Nested Case Study: Texas Wild Pig Movementmentioning
confidence: 99%
“…All wild pigs at federally inspected facilities receive an antemortem inspection and a follow-up inspection by a veterinarian for animals labeled "suspect" (57). It is imperative that wild pigs at slaughter facilities are monitored for signs of foreign animal diseases and are part of a comprehensive surveillance program.…”
Section: Nested Case Study: Texas Wild Pig Movementmentioning
confidence: 99%